Modelo press : evoluindo a adoção de práticas de engenharia de software em startups digitais - Pompermaier, Leandro Bento (2021)
Software startups or digital startups have been showing behaviors that impact the market with their new business models and growth speed. According to the flexibility required by the market and the speed that these enterprises employ in developing their products and services for quick market validation, there is crucial importance in choosing the Software Engineering practices to be used. There are several models of business maturity in the literature that are presented and discussed among entrepreneurs. One of these models was defined by the Brazilian Institute of Corporate Governance (IBGC). These models analyze the positioning of software startups and their entrepreneurs from a business point of view. Still, they do not discuss or present anything from the software engineering perspective. Frequently, in these digital startups, the practices used to develop the software which serves as the basis for the business’ product or service are neglected, adopted informally, or even isolated by some professionals in the software development teams. This informality increases the risks of generating technical debt in the different software development stages, such as the code created, the software architecture, the tests, or the documentation. This research aims to present a model of software engineering practices adopted by digital startups at different stages of business maturity, named PRESS (Portuguese acronym for Software Engineering Practices in Startups). Exploratory research was conducted using qualitative and quantitative research methods, which provided data for the proposed model’s definition. This model analyzed the following software engineering practices: development team, requirements, software testing, software architecture, project management, and development process. PRESS was developed based on the results of the studies carried out in this research. A focus group study also analyzed the suggested practices. The findings present or indicate evidence that the model can complement the business models, contributing to a better reflection or more efficient adoption of Software Engineering practices in startups, avoiding or minimizing the risks previously mentioned.